2022
DOI: 10.1007/s12672-022-00560-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune and inflammation: related factor alterations as biomarkers for predicting prognosis and responsiveness to PD-1 monoclonal antibodies in cervical cancer

Abstract: Purpose We aimed to elucidate the potential mechanisms of effective responsiveness to PD-1 monoclonal antibody and evaluate more reliable biomarkers to improve the ability to predict the populations of cervical cancer (CC) suitable for immunotherapy. Methods Peripheral blood samples of CC patients undergoing anti-PD-1 therapy were collected before and after treatment. Differentially expressed genes (DEGs) were analyzed between partial response (PR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…26 However, previous studies mainly focused on constructing prognostic models using single oxidative stress or immune features, which often suffer from limitations in robustness and generalizability. [27][28][29][30] In order to address these limitations, our study takes a comprehensive approach by incorporating both immune-related and oxidative stress-related lncRNAs. By encompassing multiscale clinical features, we aim to improve the accuracy and robustness of prognostic signatures.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, previous studies mainly focused on constructing prognostic models using single oxidative stress or immune features, which often suffer from limitations in robustness and generalizability. [27][28][29][30] In order to address these limitations, our study takes a comprehensive approach by incorporating both immune-related and oxidative stress-related lncRNAs. By encompassing multiscale clinical features, we aim to improve the accuracy and robustness of prognostic signatures.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 119 raw transcriptome data from CC patients, including 107 tissue samples and 12 peripheral blood samples, were obtained from the Gene Expression Omnibus. 14 , 15 , 16 The statistic of public datasets used in this study are shown in Table S1 . The gene expression data and corresponding clinical information of CC patients were downloaded from The Cancer Genome Atlas database (TCGA, https://xenabrowser.net or https://portal.gdc.cancer.gov ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, 119 raw transcriptome data from CC patients, including 107 tissue samples and 12 peripheral blood samples, were obtained from the Gene Expression Omnibus 14–16 . The statistic of public datasets used in this study are shown in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammation signaling represents an essential physiological cellular response of the innate immunity involved in many biological processes, such as tissue repairing and defense against pathogens. However, chronic inflammation response has been largely proved to be related to pathogenesis of several human diseases, including cancer [ 85 89 ]. In the last years, several observations have functionally linked R-loops homeostasis to the activation of the inflammation response (Fig.…”
Section: Setx Functions: From Gene Expression To Genome Integrity And...mentioning
confidence: 99%